Modern Türk Çocuk Şiirinin Dil ve Üslup Özellikleri / Language and Style Issues on Modern Turkish Child Poems - Memmedov, Cemil (Journal of History Culture and Art Research, 2013)
Abstract Poem is one of the literary kinds which are the most encountered by children. One of the important issues to be considered in being successful for child poems is their language and style properties. Language and style issues play crucial role on making poems understood and liked by children through perceiving them. We can say that it almost forms the soul and the foundation of child poems. As the style that was used in child poems in 1970-1990’s in Turkey indicates the specific reflective style of Turkish child poets, it reflects the language and style opportunities of this period as well. Nowadays, a lot of successful child poems have been written. However, the most important and obvious problem of the language and style issue about this period had become the ignorance of child’s world and their psychological condition. In addition to this, some points in child world were not analyzed detail. In the article the language and style of the child poetry which has been written in the years between 1970-1990’s was studied on the base of poems of the period. Öz Şiir çocukların en çok karşılaştıkları edebi türlerden biridir. Çocuk şiirlerinin başarılı olması için dikkat edilmesi gereken meselelerden biri de şiirdeki dil ve üslup özellikleridir. Şiirlerin çocuklar tarafından algılanarak idrak edilmesinde, sevilmesinde dil ve üslup özellikleri önemli role sahiptir. Türkiye’de 1970-1990’lı yıllarda çocuk şiirlerinde kullanılan üslup Türk çocuk şairlerinin özgün ifade tarzını gösterdiği gibi aynı zamanda dönemin dil-üslup imkânlarını da yansıtmaktadır. Bu yıllarda birçok şair tarafından başarılı çocuk şiirleri yazılmıştır. Fakat dönemin dil-üslup meselelerinde karşılaşılan en önemli özellik çocuk dünyasının, çocuk psikolojisinin ve genel olarak çocuk inceliklerinin yeterli düzeyde dikkate alınmamasıdır. Makalede 1970-1990’lı yıllarda yazılmış çocuk şiirlerindeki dil ve üslup özellikleri dönemin şiir örnekleri doğrultusunda ele alınmıştır. Les Caractéristiques du langage et du style des poèmes pour enfants dans la poésie Turque moderne (Selon les exemples des années de 1970-1990) Résumé La poésie est un des genres littéraires que les enfants rencontrent le plus souvent: il faut donc faire particulièrement attention aux caractéristiques du langage et du style dans la poésie afin que les poèmes pour enfants soient réussis, compris et aimés par les enfants. Les caractéristiques du langage et du style constituent presque exclusivement l’esprit et la base des poèmes pour enfants. Le style qu’on a utilisé dans les poèmes pour enfants dans les années de 1970-1990 montre clairement la manière originale des poètes dont les poèmes pour enfants reflètent les possibilités au niveau du langage et du style de l’époque. Dans cette période, de nombreux poètes ont écrit avec succès des poèmes pour enfants. Mais la caractéristique la plus négative au sujet des questions du langage et du style que l’on rencontre dans cette période consiste à ne pas prendre suffisamment en considération l’univers de l’enfant, sa psychologie et ses points subtils. Dans ce travail, on a examiné les caractéristiques du langage et du style des poèmes pour enfants dans les années de 1970-1990 en fonction des exemples de poèmes de l’époque concernée.